1994
DOI: 10.1007/bf00175946
|View full text |Cite
|
Sign up to set email alerts
|

Value of serum and effusion fluid CEA levels for distinguishing between diffuse malignant mesothelioma and carcinomatous pleural metastases

Abstract: Differentiation of diffuse malignant mesothelioma (DMM) from pleural carcinomatous metastases, e.g., of lung cancer (LC) may be difficult both for the clinician and the pathologist [1, 2] because of the limited diagnostic accuracy of radiologic criteria and conventional light microscopy including histochemistry [3,4]. Immunohistochemical detection of carcinoembryonic antigen (CEA) in tumor biopsy material has been shown to be a valuable diagnostic adjunct, as DMMs, unlike LCs and other carcinomas, express this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…In malignant effusions, comparative analysis highlighted the similar diagnostic performances of CEA, CA 72-4, CA 15-3 and CYFRA, clearly superior to those of CA 19-9, NSE and SCC. The diagnostic sensitivity for pleural CEA was concordant with those described in previous studies, confirming its utility in carcinomas (Rapellino et al, 1990) and its non-expression in mesotheliomas (Mezger et al, 1994). Few studies on pleural fluid have integrated CA 72-4 (Ferroni et al, 1990, Villena et al, 1996 and our results confirmed the high sensitivity of CA 72-4 in all types of adenocarcinomas, but we also noted high levels in squamous cell carcinomas.…”
Section: Discussionsupporting
confidence: 92%
“…In malignant effusions, comparative analysis highlighted the similar diagnostic performances of CEA, CA 72-4, CA 15-3 and CYFRA, clearly superior to those of CA 19-9, NSE and SCC. The diagnostic sensitivity for pleural CEA was concordant with those described in previous studies, confirming its utility in carcinomas (Rapellino et al, 1990) and its non-expression in mesotheliomas (Mezger et al, 1994). Few studies on pleural fluid have integrated CA 72-4 (Ferroni et al, 1990, Villena et al, 1996 and our results confirmed the high sensitivity of CA 72-4 in all types of adenocarcinomas, but we also noted high levels in squamous cell carcinomas.…”
Section: Discussionsupporting
confidence: 92%
“…5,22 An interesting use of CEA is the differentiation between pleural effusions due to metastatic and malignant mesothelioma. Faravelli et al reported that pleural effusions secondary to a metastatic malignancy have higher CEA levels in the pleural fluid 23 than those due to malignant mesothelioma, and Mezger et al 24 found the same to be true in serum. The results of the current study, although occurring in a small number of patients, confirm these data and support the suggestion that CEA determination in serum and pleural fluid may be a complementary tool to immunohistochemical studies for differentiating pleural effusions due to metastatic tumors from malignant mesothelioma.…”
Section: Discussionmentioning
confidence: 93%
“…Several investigators highlighted that determination of tumor marker levels might be useful in distinguishing the type of cancer. Wagner et Faravelli, found CA 15-3 level to be higher in patients with metastatic cancer compared to that of mesothelioma cases (17,18). While Porcel et al, found CEA level showing an increase of 59% in lung cancer and 71% in gastrointestinal cancer cases, they determined CA-125 level in patients with ovarium cancer as 67%.…”
Section: Discussionmentioning
confidence: 96%